Analysis of Fishing Ports in the Philippines - Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 2000)
This paper investigates fishing port development in the Philippines in light of the perceived problems of port underutilization, marine resource depletion and other issues. It notes that most of the existing regional ports were underutilized and the existing municipal ports were grossly inadequate to serve the coastal communities. The paper suggests specific measures to address these and other problems related to fishing port development
Keywords: 330; fishing ports; Fischerei; Hafenanlagen; Technische Effizienz; Philippinen